Management of the Smart Indonesia Program of the Ministry of Education and Culture for Junior High School Students - Fadhlan, Fadhlan (LPPM Universitas Ekasakti, 2023)
This research aims to determine the management of the Smart Indonesia Program in junior high schools throughout Sawahlunto City. This type of research is qualitative. The data sources in this research are data on the implementation of the Smart Indonesia Program (PIP) in junior high schools as well as direct field observations. The research informants were 21 (twenty-one) people, consisting of the Head of the Education Department, the Head of the Basic Education Division, the Head of Curriculum and Student Section, the Education Service Operator, the Principal, the School Operator, and the Community. The researcher's main data collection techniques were observation, interviews, and document study. The results of the research conclude that it is not yet optimal. Judging from the results of the research regarding the proposal, determination, distribution, and collection of funds, there are still obstacles when implementing the management of the Smart Indonesia Program in junior high schools. Because there are still many obstacles that occur in the implementation of the Smart Indonesia Program, management needs to be improved so that management of the Smart Indonesia Program is more effective and better.